The c-Abl inhibitor, Radotinib HCl, is neuroprotective in a preclinical Parkinson's disease mouse model. (20th April 2018) - Lee, Saebom; Kim, Sangjune; Park, Yong Joo; Yun, Seung Pil; Kwon, Seung-Hwan; Kim, Donghoon; Kim, Dong Yeon; Shin, Jae Soo; Cho, Dae Jin; Lee, Gong Yeal; Ju, Hyun Soo; Yun, Hyo Jung; et al.
Abstract: Accumulating evidence suggests that the non-receptor tyrosine kinase c-Abl plays an important role in the progression of Parkinson's disease (PD) and c-Abl inhibition could be neuroprotective in PD and related α-synucleinopathies. Nilotinib, a c-Abl inhibitor, has shown improved motor and cognitive symptoms in PD patients. However, issues concerning blood–brain barrier (BBB) penetration, lack of selectivity and safety still remain. Radotinib HCl is a selective Bcr-Abl kinase inhibitor that not only effectively access the brain, but also exhibits greater pharmacokinetic properties and safety profiles compared to Nilotinib and other c-Abl inhibitors. Here, we show the neuroprotective efficacy of Radotinib HCl, a brain penetrant c-Abl inhibitor, in a pre-clinical model of PD. Importantly, in vitro studies demonstrate that the treatment of Radotinib HCl protects the α-synuclein preformed fibrils (PFF)-induced neuronal toxicity, reduces the α-synuclein PFF-induced Lewy bodies (LB)/Lewy neurites (LN)-like pathology and inhibits the α-synuclein PFF-induced c-Abl activation in primary cortical neurons. Furthermore, administration of Radotinib HCl inhibits c-Abl activation and prevents dopaminergic neuron loss, neuroinflammation and behavioral deficits following α-synuclein PFF-induced toxicity in vivo . Taken together, our findings indicate that Radotinib HCl has beneficial neuroprotective effects in PD and provides an evidence that selective and brain permeable c-Abl inhibitors can be potential therapeutic agents for the treatment of PD and related α-synucleinopathies.